Quality indicators for ambulatory care for older adults with diabetes and comorbid conditions: A Delphi study. - Yelena Petrosyan; Jan M Barnsley; Kerry Kuluski; Barbara Liu; Walter P Wodchis (PLoS ONE, 2018)
BACKGROUND:An increasing number of people are living with multiple chronic conditions and it is unclear which quality indicators should be used to guide care for this population. OBJECTIVE:To critically appraise and select the most appropriate set of quality indicators for ambulatory care for older adults with five selected disease combinations. METHODS:A two-round web-based Delphi process was used to critically appraise and select quality of care indicators for older adults with diabetes and comorbidities. A fifteen-member Canadian expert panel with broad geographical and clinical representation participated in this study. The panel evaluated process indicators for meaningfulness, potential for improvements in clinical practice, and overall value of inclusion, while outcome indicators were evaluated for importance, modifiability and overall value of inclusion. A 70% agreement threshold was required for high consensus, and 60-69% for moderate consensus as measured on a 5-point Likert type scale. RESULTS:Twenty high-consensus and nineteen medium-consensus process and outcome indicators were selected for assessing care for older adults with selected disease combinations, including 1) concordant (conditions with a common management plan), 2) discordant (conditions with unrelated management plans), and 3) both types. Panelists reached rapid consensus on quality indicators for care for older adults with concordant comorbid conditions, but not for those with discordant conditions. All selected indicators assess clinical aspects of care. The feedback from the panelists emphasized the importance of developing indicators related to patient-centred aspects of care, including patient self-management, education, patient-physician relationships, and patient's preferences. CONCLUSIONS:The selected quality indicators are not intended to provide a comprehensive tool set for measuring quality of care for older adults with selected disease combinations. The recommended indicators address clinical aspects of care and can be used as a starting point for ambulatory care settings and development of additional quality indicators.